Towards a Socio-Cultural Turn in Translation Teaching: A Canadian Perspective - Whitfield, Agnes (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractWhile current translation theory is beginning to reconcile cultural and linguistic approaches to translation, this is far from the case in translation pedagogy and curriculum. This paper will argue in favour of a socio-cultural turn in translation pedagogy and curriculum design with specific reference to the Canadian/Québec context where the social, political and economic dimensions of the practice of translation, and its place within the broader area of inter-cultural communication in Canada differ depending on whether one is working into English or into French. Issues examined include redesigning curriculum to highlight the socio-cultural functions of translation, integrating culture and pedagogy, and identifying the theoretical implications of a cultural turn in translation teaching.